Getting away as a social process: "abandoned" children and the elderly in Ayacucho - Leinaweaver, Jessaca (2010)
In previous research on fostering and adoption in Ayacucho, I explored how amid the creative negotiation of discourses and spaces constructed by institutions, communities, and social structures, Ayacuchanos take up and produce new social relations. This article discusses the opposite process: undoing kinship, and the social process of abandonment or distancing. When a person is withdrawn from his or her family or community, those who remain come to understand themselves as certain kinds of persons. The case studies considered here, collected through careful participant observation and ethnographic interviews recorded between 2001 and 2007, reveal how, after social distancing or abandonment, the individuals who do the distancing reinterpret themselves as subjects who are improving themselves and becoming modern.